Analysis of the 2012–2013 Torreperogil-Sabiote seismic swarm. (October 2016) - Hamdache, M.; Peláez, J.A.; Henares, J.; Damerdji, Y.; Sawires, R.
Abstract: This study analyses the temporal clustering, spatial clustering, and statistics of the 2012–2013 Torreperogil-Sabiote (southern Spain) seismic swarm. During the swarm, more than 2200 events were located, mostly at depths of 2–5 km, with magnitude event up to m bLg 3.9 ( M w 3.7). On the basis of daily activity rate, three main temporal phases are identified and analysed. The analysis combines different seismological relationships to improve our understanding of the physical processes related to the swarm's occurrence. Each temporal phase is characterized by its cumulative seismic moment. Using several different approaches, we estimate a catalog completeness magnitude of m c ≅ 1.5. The maximum likelihood b -value estimates for each swarm phase are 1.11 ± 0.09, 1.04 ± 0.04, and 0.90 ± 0.04, respectively. To test the hypothesis that a b -value decrease is a precursor to a large event, we study temporal variations in b -value using overlapping moving windows. A relationship can be inferred between change in b -value and the regime style of the rupture. b -values are indicators of the stress regime, and influence the size of ruptures. The fractal dimension D 2 is used to perform spatial analysis. Cumulative gamma and beta functions are used to analyse the behaviour of inter-event distances during the earthquake sequence. Highlights: Torreperogil-Sabiote seismic swarm. b-value as precursory. b-value and regime style of rupture. Fractal dimension, Markov Chain, Gamma and Beta cumulative distribution.